Corrigendum: "Combinatorial Strategies for the Induction of Immunogenic Cell Death" - Bezu, Lucillia; Gomes-da-Silva, Ligia C; Dewitte, Heleen; Breckpot, Karine; Fucikova, Jitka; Spisek, Radek; Galluzzi, Lorenzo; Kepp, Oliver; Kroemer, Guido (Frontiers in immunology, 2015)
[This corrects the article on p. 187 in vol. 6, PMID: 25964783.].
Keywords: HMGB1 protein; calreticulin; endoplasmic reticulum stress; ATP; autophagy; type I interferon